A Study of Emotional Intelligence of Primary Teachers in Relation to Gender, School Type & Teaching Experience - Prof. Kavita Varma, Dr. Shashi Chaudhary, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: In the present research study, emotional intelligence has been studied with reference to the gender, school type and teaching experience of primary teachers of Agra and Mathura district. In this study Gender taken as male& female, School Type taken as government & non-government and Teaching experience of teachers divided into four categories: first category (less than 5 years of teaching experience), second category (5-15 years of teaching experience), third category (16-25 years of teaching experience), fourth category (more than 25 years of teaching experience). A total of 800 teachers working in primary schools have been selected for sample through random method. Teachers Emotional Intelligence Inventory standardized tool made by Dr. Subhra Mangal, It consists of 100 items consisting four components each having 25 items. In overall result of the study there is no meaningful difference found in emotional intelligence of primary teachers regarding gender, School types and teaching experiences.